2013
DOI: 10.1111/bcpt.12154
|View full text |Cite
|
Sign up to set email alerts
|

The Neuro‐Immune Axis: Prospect for Novel Treatments for Mental Disorders

Abstract: Disturbed bidirectional pathways between the (central) nervous system and immune system have been implicated in various mental disorders, including depressive and neurodevelopmental disorders. In this minireview, the role of the neuroimmune axis and its targetability in relation to major depression and autism spectrum disorder will be discussed. All together, the management of these and possibly other multi-factorial mental disorders needs a new and integrated therapeutic approach. Pharmacologically bioactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 122 publications
(145 reference statements)
0
16
0
Order By: Relevance
“…Others support this hypothesis as well [6][7][8][9][10]. Microbial cells harbored within the human gut and elsewhere are being studied to understand their multifunctional properties and their ability to affect physiological activities in their "host" organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others support this hypothesis as well [6][7][8][9][10]. Microbial cells harbored within the human gut and elsewhere are being studied to understand their multifunctional properties and their ability to affect physiological activities in their "host" organism.…”
Section: Discussionmentioning
confidence: 99%
“…This is possible because of common receptors on immune and neural cells, which is the hallmark of neuroimmunology. Importantly, what is causing this abnormal immune cell non-specific excitation may be the gut microbiome, which is constantly producing chemical messengers and other substances while potentially undergoing shifts in the ratios of its bacterial community [7,10,18,30,31]. Thus, one of the stressors may induce a state of inappropriate activation on a wide scale based on the numbers and kinds of bacteria present.…”
Section: Consolidationmentioning
confidence: 99%
“…Galactose is an important metabolites involved in the formation of glycans featuring galactose and its derivatives which were essentially bound by galectins [51], [52]. Converging evidence suggested that galectins play an important role in neuroinflammation and brain development and function [53][55], and Kraneveld et al reported that dietary or pharmacological modulation with small molecules targeting the galectin response in neurodevelopment disorders such as MDD could be a future therapeutic approach [56]. Although galactose's role in MDD is not clear, the foregoing reports implied that galactose may be involved in galectin-glycan interactions associated with the neuro-immune axis in mental disorders such as MDD and ELS/MDD.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the gut-brain axis, also known as the neuroimmune axis, has been found to contribute to the pathophysiology of many neurodevelopmental diseases such as depression and autism. 32 The majority of studies have focused on the impact of microbiota on CNS function and stress perception. Stress and the associated change in the HPA axis can also influence microbiota composition in the gut.…”
Section: Brain-gut Interactionmentioning
confidence: 99%